PERAN STRATEGIS KOMUNIKASI PARIWISATA DALAM MEMPERKUAT BRANDING DESTINASI SUPER PRIORITAS DANAU TOBA, SUMATERA UTARA - Sihombing, Bantors; Panjaitan, Hadi (Akademi Pariwisata Darma Agung, 2025)
The designation of Lake Toba as one of Indonesia's five Super Priority Tourism Destinations (DPSP) requires massive and integrated promotional efforts. This research aims to analyze the strategic role of tourism communication in the promotion and strengthening of Lake Toba's branding. Using a qualitative approach with a descriptive-analytical method, data were collected through in-depth literature review, observation of digital media platforms, and document analysis from relevant stakeholders. The results indicate that tourism communication plays a central role in shaping image, disseminating information, and persuading potential tourists. The current implementation of tourism communication for Lake Toba utilizes various channels, particularly digital media such as social media (Instagram, TikTok, YouTube) and official websites. However, the main challenge is the lack of message integration among stakeholders (government, private sector, and community), resulting in a fragmented brand image. Effective communication serves not only as a promotional tool but also as a bridge to align the vision and actions of stakeholders. An integrated communication orchestration is needed, combining the power of digital media with the authenticity of interpersonal communication and local wisdom to build a strong and sustainable image for Lake Toba.